PRESENCE DETECTION SYSTEMS - EFFICIENCY OF USE, BEST PRACTICE - Vikainis, Roberts; Talapins, Sergejs; Matvejevs, Romans (Border Security and Management, 2023)
One of the features of the development of modern society is the growing need to restrict access to various objects. The main task of the State Border Guard is to ensure the inviolability of the state border, including the prevention of illegal crossing of the state border. Nowadays, presence detection systems are often used for this purpose - devices or functions of a security television system that generate an alarm when movement is detected in the field of view of the camcorder. The aim of the current study is to analyze the efficiency of the use of presence detection systems used in the structural units of the State Border Guard.